The Effect of GHRM on Environmental Performance Mediated by Employee Environmental Knowledge at GL Zoo - Trikurnian, Aloysius Dhimas; Rahayu, Caecilia Wahyu Estining (Journal of Management and Business Environment (JMBE), 2025)
This study aims to determine the effect of green human resource management (GHRM) on environmental performance mediated by employee environmental knowledge. This study uses a quantitative approach with three independent variables: green recruitment and selection, green training and development, green performance management and appraisal, and the dependent variable, environmental performance, with the mediating variable of employee environmental knowledge. Data were collected using a questionnaire tested for validity and reliability before being distributed and analyzed using the SmartPLS3 application. The sample comprised all Gembira Loka Zoo (GL Zoo) employees, totaling 100 respondents. The technique used in non-probability sampling is purposive sampling. The results showed that green training and development directly affect environmental performance, and employee environmental knowledge fully mediates the effect of green performance management and appraisal on environmental performance.